PENGEMBANGAN MODEL INKUBATOR BISNIS PERGURUAN TINGGI - Suwandi, Suwandi (Jurnal Penelitian Humaniora, 2015)
This research aims at describing business incubator models in university. It uses a grounded research method. The research is conducted in 20 state universities. Initially, it is conducted by strategic study, exploration study, crystallization of the study, and model dissemination. Data are obtained through questionnaire and interview. Data are analyzed by the following processes: coding, data entry, and tabulating. From the findings, it can be concluded that business incubator is commonly carried out in relation to society services and tends to be conducted out of university (out will). Along with campus autonomy, internal elements need to develop through business unit incubator in university. There are typologies related t incubator model in university. They are (1) not yet exist, (2) is pioneered, (3) exist, but undeveloped, (4) no business incubator, but there are commercial incubator units (in wall), (5) business incubators exists but they are "˜out’ oriented (out will), and (6) complete business incubators (in wall and out wall). To develop, it needs some processes in relation to the typologies: (1) preparation, (2) forming, (3) re-running, (4) completing, (5) in wall forming and developing, (6) in wall and out wall developing.